Exploring mental health: a comparative study of Western and Islamic psychological approaches - Abdul Razak, Mohd Abbas; Abdul Razak, Abdul Latif; Zaroum, AbdulHamid Mohamed Ali (Centre for Islamisation (CENTRIS), IIUM, 2024)
This research is both timely and crucial, as the world grapples with a growing mental health crisis. As society embraces a more modern lifestyle, it also faces an increase in mental health challenges. Despite efforts by various organizations and concerned parties worldwide, a permanent solution remains elusive. This study explores the connection between human nature, mental health, and psychotherapy, comparing Western psychological frameworks with Islamic psychology. Mental health issues often stem from a deeper understanding of human nature, and psychotherapy aims to address these concerns by improving one's relationship with oneself, others, and the environment. In Western thought, mental health and psychotherapy are generally approached in a secular, scientific context, relying on psychological theories such as those of Freud, Jung, and humanistic psychologists. These theories focus on human experience and behaviour, offering therapeutic techniques grounded in empirical evidence, such as cognitive-behavioral therapy (CBT) and psychodynamic therapy. However, Western psychology has limitations, often overlooking cultural, existential, and spiritual factors that may be critical in treating complex mental health conditions. In contrast, Islamic psychology offers a more holistic perspective, integrating physical, emotional, psychological, and spiritual dimensions of human well-being. It draws on Islamic teachings, including the Qur'an, Hadith, and the wisdom of Islamic scholars, providing both preventive and remedial approaches to mental health. Islamic psychology emphasizes practices such as prayer, meditation, gratitude, and social relationships as preventive measures, fostering a sense of hope and purpose that contributes to mental well-being. This research uses a qualitative, contrastive methodology, drawing on textual analysis from books on psychology, Qur'anic teachings, and Hadith/Sunnah to comprehensively compare Western and Islamic approaches to mental health and psychotherapy.